Osculating Spheres of a Semi Real Quaternionic Curve in E24 - Bektas, O.; Gurses, N. Bayrak; Yuce, S. (EUROPEAN JOURNAL PURE & APPLIED MATHEMATICS, 2014)
In this study, we define the osculating spheres of a semi real quaternionic curve in semi-Euclidean spaces E-1(3) and E-2(4). We give the equation of the osculating spheres with respect to Frenet frames {t(0), n(10), n(20) } and {T-0, N-10, N-20, N-30}.
Keywords: Osculating sphere; semi real quaternionic curve; semi-Euclidean space; Mathematics